Communicating with One Another Toward a Psychology of Spontaneous Spoken Discourse - Kowal, Sabine (Cognition and Language: A Series in Psycholinguistics, 2008)
"A unique view of language studies throughout the 20th and into the 21st centuries: where the mainstream emphasis has been, what has been missing, and what remedies are needed. In other words, this book is a call for a paradigm shift in the study of oral communication. It is a must read for people interested in language use, as well as for specialists in language studies." Camelia Suleiman, Ph.D., Florida International University, Miami, FL, USA "The authors have identified crucial theoretical and methodological assumptions that have hampered scholarship on language use. Their critical assessment is grounded in nuanced theoretical analysis and rigorous empirical studies. As a result, they reveal the complexity, elegance, and moral aspects of day to day dialogical communication." Kevin P. Weinfurt, Ph.D., Duke University, Durham, NC, USA In contrast to traditional approaches of mainstream psycholinguists, the authors of Communicating with One Another approach spontaneous spoken discourse as a dynamic process, rich with structures, patterns, and rules other than conventional grammar and syntax. Daniel C. O'Connell and Sabine Kowal thoroughly critique mainstream psycholinguistics, proposing instead a shift in theoretical focus from experimentation to field observation, from monologue to dialogue, and from the written to the spoken. They invoke four theoretical principles: intersubjectivity, perspectivity, open-endedness, and verbal integrity. Their analyses of historical and original research raise significant questions about the relationship between spoken and written discourse, particularly with regard to transcription and punctuation. With emphasis on political discourse, media interviews, and dramatic performance, the authors review both familiar and unexplored characteristics of spontaneous spoken communication, including: The speaker's use of prosody. The functions of interjections. What fillers do for a living. Turn-taking: Smooth and otherwise. Laughter, applause, and booing: from individual listener to collective audience. Pauses, silence, and the art of listening. The paradigm shift proposed in Communicating with One Another will interest and provoke readers concerned about communicative language use - including psycholinguists, sociolinguists, and anthropological linguists.